2019
DOI: 10.1021/acssuschemeng.9b05042
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of a Metallic NiCo Dimer Anchored on a C2N–Graphene Matrix Promotes the Electrochemical CO2 Reduction Reaction

Abstract: Gaining mechanistic insights into the active site is essential to rational design of a high-performance cathode catalyst for the electrochemical CO2 reduction reaction (CO2 RR). Here, by means of density functional theory and computational hydrogen electrode methods, we investigated synergy of a metallic NiCo dimer anchored on a C2N graphene matrix for promoting the CO2 RR. It is found that heterometallic NiCo@C2N (U L = −0.25 V) outperforms homometallic Co2@C2N (U L = −0.30 V) and Ni2@C2N (U L = −0.67 V) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 61 publications
1
62
1
Order By: Relevance
“…Above, we have demonstrated that constructing donor–acceptor couples of dual-metal sites is a powerful method to boost NRR. In fact, the generality of this proposed strategy for N 2 activation, i.e., the pull–pull effect based on dual-metal sites to activate the N≡N bond, can also be extended to other 2D porous materials such as g-C 2 N, 25 , 36 phthalocyanine, 26 N-doped graphene, 19 24 and so on. As shown in Figure 6 a, the optimized structures of FeMo dual-metal were anchored on N-doped graphene by forming N-coordinated N 3 Fe-MoN 3 with an average absorption energy of −6.0 eV per metal atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above, we have demonstrated that constructing donor–acceptor couples of dual-metal sites is a powerful method to boost NRR. In fact, the generality of this proposed strategy for N 2 activation, i.e., the pull–pull effect based on dual-metal sites to activate the N≡N bond, can also be extended to other 2D porous materials such as g-C 2 N, 25 , 36 phthalocyanine, 26 N-doped graphene, 19 24 and so on. As shown in Figure 6 a, the optimized structures of FeMo dual-metal were anchored on N-doped graphene by forming N-coordinated N 3 Fe-MoN 3 with an average absorption energy of −6.0 eV per metal atom.…”
Section: Resultsmentioning
confidence: 99%
“… 19 24 In particular, NiCo heteronuclear dimer anchored on g-C 2 N exhibited higher catalytic activity toward CO 2 RR into CH 4 than CoCo and NiNi homonuclear dimers. 25 For NRR, several heteronuclear metal-dimers anchored on N-doped graphene and phthalocyanine were proposed to have an improved catalytic activity than the corresponding homonuclear DACs. 26 , 27 Very recently, Chen et al 28 obtained a NRR Faradaic efficiency up to 67.8% by constructing donor–acceptor couples of Au and Ni nanoparticles on N-doped carbon.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the complexity of the CO 2 RR mechanism and the multifarious reaction products, more experimental and theoretical studies are required. TM 2 @phthalocyanine Mn 2 @phthalocyanine CH 3 OH −0.84 2017 [123] TM 2 @C 2 N Cu 2 @C 2 N CH 4 /C 2 H 4 −0.23 (CH 4 )/−0.76 (C 2 H 4 ) 2018 [124] Ni 2 , Co 2 , NiCo@C 2 N NiCo@C 2 N CH 4 −0.23 2019 [125] TM 1 /TM 2 @C 2 N CuCr/CuMn@C 2 N CH 4 −0.37/−0.32 2020 [50] TM 1 /TM 2 @N 6 -C CuMn, NiMn, NiFe@N 6 -C CO ≈−0.43 (CuMn); ≈−0.45 (NiFe); ≈−0.65 (NiMn) 2020 [52c] Fe 2 @holey N-doped carbon monolayers Fe 2 @C 2 N C 2 H 5 OH −0.70 2020 [126] Fen@graphdiyne (n = 1-4) Fe 2 @graphdiyne CH 4 −0.29 2020 [127] www.afm-journal.de www.advancedsciencenews.com…”
Section: (19 Of 25)mentioning
confidence: 99%
“…Several theoretical predictions on the ability of C 2 N and metal composites to act as catalysts for diverse applications followed (e.g., HCOOH dehydrogenation, seawater desalination, and photocatalytic and electrocatalytic water splitting activity). [ 67–77 ] The predicted multipodal strong binding sites [ 66 ] play an important role when C 2 N combines with CO 2 , ionic liquids, and metal ions, such that C 2 N exhibits excellent gas adsorption/separation, supercapacitor, and battery performance, [ 38,40 ] which is discussed in detail in subsequent sections. Moreover, due to these unique pores, C 2 N itself can be used as a catalyst as well as a support, which can strongly bind large amounts of single metal atoms.…”
Section: Intrinsic Features Of C2nmentioning
confidence: 99%